Synthesis and Vibrational Spectra of Metal Halide Complexes of 3 5 Lutidine in Relation to their Structures - Yurdakul, Şenay; Davies, J. Eric D.; AKYÜZ, SEVİM (Taylor and Francis Online, 1997)
The synthesis and the results of an infrared and Raman spectroscopic study are reported for metal(II) halide 3,5-lutidine (3,5-dimethylpyridine) complexes, M(3,5L)2X2, M = Cd or Zn, X = Cl, Br or I; M = Co, Cu or Hg, X = Cl or Br; M = Mn, Fe or Ni, X = Cl, 3,5L = 3,5-lutidine. Vibrational assignments are given for all the observed bands. Some structure-spectra correlations were found. For a given series of isomorphous complexes the sum of the difference of the values of the vibrational modes of 3,5-lutidine between the free ligand as liquid and the complexed ligand was found to increase in the order of the second ionization potentials of the metals. The frequency shifts were also found to depend on the halogen.